2009
DOI: 10.3748/wjg.15.1764
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of linked angina and gastroesophageal reflux disease in general practice

Abstract: AIM:To evaluate the association between gastroesophageal reflux diseases (GERD) and coronary heart diseases. METHODS:One thousand nine hundred and seventy consecutive patients who attended our hospital were enrolled. All of the patients who first attend our hospital were asked to respond to the F-scale questionnaire regardless of their chief complaints. All patients had a careful history taken, and resting echocardiography (ECG) was performed by physicians if the diagnostic necessity arose. Patients with ECG s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“…41 It is possible that when a clopidogrel-receiving patient presents with nonspecific upper gastrointestinal chest pain, the potential exists for the patient to be prescribed a PPI, even though the pain was a consequence of myocardial ischemia. 42 Patients may receive both PPIs and antianginal drugs; retrospective analyses of health care system databases suggest that 1-year MACE rates were significantly higher among patients who were prescribed PPI therapy within 30 days of an MACE, and the use of rescue nitroglycerin among patients receiving both clopidogrel and a PPI was double the rate of patients receiving clopidogrel alone. 41 Physicians commonly prescribe PPIs with antianginal drugs, as epigastric discomfort or gastroesophageal reflux disease presents as chest pain.…”
Section: Discussionmentioning
confidence: 98%
“…41 It is possible that when a clopidogrel-receiving patient presents with nonspecific upper gastrointestinal chest pain, the potential exists for the patient to be prescribed a PPI, even though the pain was a consequence of myocardial ischemia. 42 Patients may receive both PPIs and antianginal drugs; retrospective analyses of health care system databases suggest that 1-year MACE rates were significantly higher among patients who were prescribed PPI therapy within 30 days of an MACE, and the use of rescue nitroglycerin among patients receiving both clopidogrel and a PPI was double the rate of patients receiving clopidogrel alone. 41 Physicians commonly prescribe PPIs with antianginal drugs, as epigastric discomfort or gastroesophageal reflux disease presents as chest pain.…”
Section: Discussionmentioning
confidence: 98%
“…9,10 There also have been a few epidemiological studies exploring the link between GERD and cardiovascular diseases. 11,12 Using the UK General Practice Research Database, Ruigómez et al 11 demonstrated that patients with GERD had an increased risk of subsequent diagnosis of angina.…”
Section: Discussionmentioning
confidence: 99%
“…Heartburn occurs predominantly in the upper gastrointestinal tract (GIT) and is a key presentation in gastroesophageal reflux disease (GERD) and gastritis. 1,2 GERD and gastritis, the most common debilitating conditions of the GIT, are characterized by an orderly occurrence of injury or inflammation in the innermost layer of the oesophagus and stomach. 3,4 Several risk factors increase the frequency and severity of the condition including, smoking, high body mass index, limited physical activity, and certain medications (such as anti-inflammatory and cytotoxic drugs).…”
Section: Introductionmentioning
confidence: 99%